Social capital and self‐rated health: A cross‐sectional study of the general social survey data comparing rural and urban adults in Ontario. (30th September 2018) - Buck‐McFadyen, Ellen; Akhtar‐Danesh, Noori; Isaacs, Sandy; Leipert, Beverly; Strachan, Patricia; Valaitis, Ruta
Abstract: The concept of social capital shows great promise for its potential to influence individual and population health. Yet challenges persist in defining and measuring social capital, and little is known about the mechanisms that link social capital and health. This paper reports on the quantitative phase of a sequential explanatory mixed methods study using data from Canada's 2013 General Social Survey (data collected 2013–14). An exploratory factor analysis revealed six underlying dimensions of social capital for 7, 187 adults living in Ontario, Canada. These factors included trust in people, neighbourhood social capital, trust in institutions, sense of belonging, civic engagement, and social network size. A logistic regression indicated that having high Trust in People and Trust in Institutions were associated with better mental health while high Trust in Institutions, Sense of Belonging, and Civic Engagement were associated with better physical health. When comparing rural and urban residents, there were no differences in their self‐reported health, nor did social capital influence their health any differently, despite rural residents having higher social capital scores. The study findings are important for understanding the nature of social capital and how it influences health, and provide direction for targeted health promotion strategies.